Paroxysmal Nocturnal Hemoglobinuria: A Chronic Rare Acquired Hemolytic Anemia in a Middle-aged Female with Thrombotic Complications and Multi-system Involvement (Journal of Medicine, 2017)
Paroxysmal Nocturnal Hemoglobinuria (PNH) is an acquired coombs negative hemolytic anemia, the hallmark of which is chronic intravascular hemolysis, thrombophilia and their sequelae owing to the deficiency of several surface proteins on blood cell membranes. In this case a middle-aged female presents with severe anemia requiring repeated blood transfusion and recurrent deep vein thrombosis (DVT). She had been hospitalized in multiple occasions in multiple centers without any satisfactory diagnosis. The constant laboratory features were that of hemolytic anemia, thrombocytopenia and a negative coombs test; although reticulocyte count had not been elevated. Lastly Blood flow cytometry revealed PNH clones. Although excellent improvement of the clinical features of PNH can be achieved by treatment with Eculizumab, we could not offer that to our patient due to its unavailability in Bangladesh. She was discharged with advice for Hematopoietic Stem Cell Transplantation (HSCT) after her symptoms improved with symptomatic management. High degree of suspicion and appropriate application of clinical knowledge is necessary to make such a diagnosis early in the disease process, for prompt initiation of treatment and thus minimizing complications.J MEDICINE July 2017; 18 (2) : 123-127